Cultural Acculturation Among Students from Outside Java: A Study Beyond Java's Borders: Akulturasi Budaya di Kalangan Mahasiswa dari Luar Jawa: Studi di Luar Batas Jawa - Ana Fieka Niswatul Ilmy; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores cultural acculturation among students from outside Java at Muhammadiyah University Sidoarjo (Umsida). Utilizing qualitative methods, including purposive sampling, interviews, and observations, the research reveals swift adaptation in language, accents, habits, and cuisine. While students embrace Javanese culture through interactions and active participation, they maintain their original identity. This research contributes valuable insights into the nuanced dynamics of cultural assimilation within educational contexts, emphasizing the importance of fostering cultural understanding and inclusivity. Highlights : Swift Assimilation: Non-Javanese students at Umsida rapidly adapt to local language, accents, habits, and cuisine. Identity Maintenance: Despite cultural assimilation, students consciously retain aspects of their original identity. Educational Dynamics: The study sheds light on the intricate dynamics of cultural exchange within the educational setting, emphasizing the need for inclusivity and cultural understanding. Keywords: Cultural Adaptation, Non-Javanese Students, Umsida, Intercultural Communication, Identity Preservation